Hambatan Penegakan Hukum terhadap Pelaku Tindak Pidana Pencurian Benda Cagar Budaya di Kupang Nusa Tenggara Timur (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The purpose of this study is the obstacles to law enforcement against perpetrators of criminal acts of theft of cultural heritage objects in Kupang, East Nusa Tenggara. This research is an empirical juridical research that examines a legal event that occurs through a statute cause approach. Data collection is carried out with two events, namely interviews and document studies. The data obtained is then presented descriptively qualitative. The results showed that the obstacles experienced by the community and law enforcement officials are: the absence of reports to the police and coordination with other stakeholders; the caretaker's mistake in understanding evidence; stakeholders who observe cultural heritage have not functioned optimally; and there is no PPNS cultural heritage in NTT. Prevention efforts taken in the form of prevention include: organizing cultural heritage promotion and counseling campaigns; providing training or technical guidance to all cultural heritage caretakers in NTT; the government supports the presence of the Cultural Preservation Agency (BPK); and collaborating with stakeholders. Law enforcement against criminal acts of theft of cultural heritage objects is still not optimal. Therefore, suggestions for the results of this study are the socialization of cultural heritage protection and cultural heritage laws comprehensively. All stakeholders must be more adaptive and responsive. BPK needs to cooperate with local governments and related institutions to draft a special regulation or law governing the establishment of a special agency for the supervision of cultural heritage sites. Make a government regulation regarding the establishment of a special cultural heritage police.